A Plea for Diversity in Eating Disorders Research - Halbeisen, Georg; Brandt, Gerrit; Paslakis, Georgios (Frontiers in Psychiatry, 2022)
Eating disorders (EDs) are often stereotyped as affecting the SWAG, that is, as affecting mostly skinny, White, affluent girls. Over the last decade, however, significant progress has been made toward increasing diversity in ED research. There is consensus that EDs affect individuals of all genders, ages, sexual orientations, ethnic, and socio-economic backgrounds, with recent studies exploring social determinants of ED etiology, ED presentation, and developing diversity-affirming ED assessments. This article provides a brief summary of current developments related to diversity as a research theme, and proposes different perspectives towards further improving diversity in ED research. Specifically, we argue for exploring the role of diversity in ED treatment settings and outcomes, for pursuing diversity-oriented research proactively rather than as a reaction to issues of underrepresentation, and for integrating diversity across different areas of medical education and trainings in psychotherapy. Limitations with respect to the paucity of research, and the link between diversity as a research theme and ED-related workforce diversity are discussed.